The Influence of Corporate Communication Strategy and Customer Value Creation Toward Creation of Reputation (Case Study at Len-Indonesian State Owned Company) - Achmad Rizal (Universal Journal, 2026)
The objectives of this research are to identify and analyze the corporate communication strategy, customer value creation, corporate reputation, and the influence of corporate communication strategy and customer value creation on the development of corporate reputation. This study employed a descriptive and verificative research design using descriptive survey and explanatory methods. The respondents were selected through stratified random sampling, resulting in a sample of 55 respondents. Data were collected through library research, observation, and questionnaires. The data were analyzed using path analysis. The results indicate that corporate communication strategy and customer value creation simultaneously influence the creation of the corporate reputation of Len Industri Group by 53.7%. Partially, corporate communication strategy has a significant influence on corporate reputation, contributing 47.2%, whereas customer value creation contributes 5.1% and does not have a statistically significant effect on the creation of corporate reputation.